Pengembangan Video Tutorial Sulam Pita Pada Elemen Eksperimen Tekstil dan Desain Hiasan - Situmorang, Deriwati (Jurnal Riset Multidisiplin dan Inovasi Teknologi, 2025)
The objectives of this study were 1) To describe the level of validity of video tutorial media for ribbon embroidery in the Textile and Design Experiment element of phase F at SMK Negeri 3 Probolinggo. 2) To describe the learning outcomes of students after the application of video tutorial media for ribbon embroidery in the element of Textile and Design Experiment phase f at SMK Negeri 3 Probolinggo. This research is a development research or R&D with ADDIE model. The research subjects involved 32 students of class XI Fashion Management of SMK Negeri 3 Probolinggo in the product trial.  Data collection techniques are video tutorial validity assessment and student learning outcomes assessment. Data collection instruments with video tutorial validity assessment sheets, test assessment sheets and assessment rubrics. The data analysis technique used is descriptive with the results of the study showing that it is used in this study with the results of the study showing 1) the level of validity of ribbon embroidery video tutorials on textile experimental elements and decorative designs in terms of linguists, media experts and material experts reached an average score of 4.66 with a very valid category. 2) Student learning outcomes achieved 100% classical completeness.